Allometric relationship and meat yield of Chama pacifica broderip, 1835 from the Gulf of Antalya, Turkey - TanrÄ±verdi, Raziye; Gökoğlu, Mehmet; Korun, Jale (Universitas Malikussaleh, 2020)
In this study, the allometric relationship and the meat yield of the large Pacific jewel-box Chama pacifica Broderip, 1835 were investigated. C. pacifica samples were by scuba diving at depths of 3-8 m in the Gulf of Antalya. The relationship of total shell length and total shell weight was determined as TW = 2.2693*TSL 2.5327 (R2= 0.69). The mean flesh weight and mean meat yield were determined to be 11,07±0.445 g and 6.84±0.18%, respectively. This research revealed the meat yield data of C. pacifica and its potential importance as a food source.Keywords: Chama pacifica; Pacific jewel-box; flesh weight; meat yield; allometric relationship